Teachers in Learning Islamic Religious Education Post the Covid-19 Pandemic at Mutiara Bangsa Elementary School Pringsewu Lampung - Irmawati, Irmawati; Mispani, Mispani; Suadi, Suadi; Amirudin, Amirudin (Assyfa Journal of Islamic Studies, 2024)
This research aims to explore the learning strategies implemented by Islamic Religious Education teachers at Mutiara Bangsa Elementary School Pringsewu, Lampung, after the COVID-19 pandemic. Using a qualitative descriptive approach, this research involves primary data from school principals, deputy principals, and teachers, as well as secondary data in the form of important documentation related to data on teachers, students, and infrastructure. Data collection techniques include observation, interviews, and documentation. Data analysis was carried out in three stages: data reduction, data presentation, and conclusion. The research results show that teachers implement strategies to improve the quality of learning through careful curriculum planning, organizing teaching tasks, and comprehensive evaluation. Evaluation is carried out through written assessments, interviews, and accidental oral assessments. Apart from that, teachers also strengthen teaching materials by habituating good behavior among students, aiming to form good morals automatically without needing to think long. This research concludes that the strategies implemented are quite effective in increasing students' interest in learning, although there are still some students who have not achieved the expected results. More intensive efforts are needed to achieve better educational outcomes in the future.